Analysis of Jmjd6 cellular localization and testing for its involvement in histone demethylation. - Hahn, P; Wegener, I; Burrells, A; Böse, J; Wolf, A; Erck, C; Butler, D; Schofield, C; Böttger, A; Lengeling, A (Public Library of Science, 2010)
BACKGROUND: Methylation of residues in histone tails is part of a network that regulates gene expression. JmjC domain containing proteins catalyze the oxidative removal of methyl groups on histone lysine residues. Here, we report studies to test the involvement of Jumonji domain-containing protein 6 (Jmjd6) in histone lysine demethylation. Jmjd6 has recently been shown to hydroxylate RNA splicing factors and is known to be essential for the differentiation of multiple tissues and cells during embryogenesis. However, there have been conflicting reports as to whether Jmjd6 is a histone-modifying enzyme. METHODOLOGY/PRINCIPAL FINDINGS: Immunolocalization studies reveal that Jmjd6 is distributed throughout the nucleoplasm outside of regions containing heterochromatic DNA, with occasional localization in nucleoli. During mitosis, Jmjd6 is excluded from the nucleus and reappears in the telophase of the cell cycle. Western blot analyses confirmed that Jmjd6 forms homo-multimers of different molecular weights in the nucleus and cytoplasm. A comparison of mono-, di-, and tri-methylation states of H3K4, H3K9, H3K27, H3K36, and H4K20 histone residues in wildtype and Jmjd6-knockout cells indicate that Jmjd6 is not involved in the demethylation of these histone lysine residues. This is further supported by overexpression of enzymatically active and inactive forms of Jmjd6 and subsequent analysis of histone methylation patterns by immunocytochemistry and western blot analysis. Finally, treatment of cells with RNase A and DNase I indicate that Jmjd6 may preferentially associate with RNA/RNA complexes and less likely with chromatin. CONCLUSIONS/SIGNIFICANCE: Taken together, our results provide further evidence that Jmjd6 is unlikely to be involved in histone lysine demethylation. We confirmed that Jmjd6 forms multimers and showed that nuclear localization of the protein involves association with a nucleic acid matrix.